Kebebasan Individu dalam Tinjauan Filsafat Eksistensialisme Jean Paul Sartre - Muhamad Fauzan; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
In compiling this study, researchers used qualitative methods with an approach to literature study. The result of this study is that humans can become independent as long as their actions benefit mankind. Sartre has two distinct themes in his philosophy of consciousness (existence) and freedom. Freedom became an essential theme in the philosophy of Sartre. Sartre analyzes much about freedom and the way of human existence. According to Sartre, there are two "etres" (existings): "en soi" (for oneself) and "pour soi" (for oneself). Existentialism was a stream of philosophy born around the 19th and 20th centuries. Existentialism aims to answer the question of how man should live after the illusion of his freedom has been destroyed by so many catastrophes in history. Historical disasters destroy the illusion of human freedom. Sartre asserts that freedom is the essence of man, since the essence will be present when man is in existence, and freedom is the most free way to exist. With freedom, man will not be restrained in action.